A crash course in leading through change and challenges. Issue 7 (23rd October 2017) - Skipworth, Stan
Abstract : When I was a young traffic enforcement officer, my responsibilities included investigating traffic collisions of all types. Over the course of a few years, I was sent to what would seem to be hundreds of the most common collisions you would expect to see: a vehicle traveling in one direction that would be struck by a vehicle coming from another direction. From those several‐hundred traffic accidents I responded to, investigated, and reported on, a small number stood out for their uniqueness.